PENGARUH INFLASI, INDEKS PERSEPSI KORUPSI, DAN NILAI TUKAR TERHADAP FOREIGN DIRECT INVESTMENT DI KAWASAN ASEAN-5 DALAM PERSPEKTIF EKONOMI ISLAM (ANALISIS DATA PANEL 2019-2024) - Utama, Ridho; Malik, Anas; Rahman, Taufiqur (Investama : Jurnal Ekonomi dan Bisnis, 2025)
The objective of this study is to analyze the influence of inflation, the Corruption Perceptions Index, and the exchange rate on Foreign Direct Investment (FDI) in the ASEAN-5 region from the perspective of Islamic economics during the 2019–2024 period. This research employs a quantitative method using a panel data approach. The selection of the most appropriate regression model was conducted through the Chow test, Hausman test, and Lagrange Multiplier test, which collectively identified the Random Effects Model (REM) as the most suitable. Data analysis was performed using Eviews 13 software. The findings reveal that both inflation and the Corruption Perceptions Index have a positive and significant impact on FDI, whereas the exchange rate exerts a negative but statistically insignificant effect on FDI. Collectively, inflation, the Corruption Perceptions Index, and the exchange rate significantly influence FDI, as indicated by an F-statistic probability value of 0.000047. From the perspective of Islamic economics, these results underscore the importance of economic stability, good governance, and equitable wealth distribution in fostering a healthy and sustainable investment climate.